Formation of Advanced Glycation End Products During CAPD - Tauer, Andreas; Zhang, Xiaohong; Schaub, Thomas; Zimmeck, Thomas; Niwa, Toshimitsu; Passlick-Deetjen, Jutta; Pischetsrieder, Monika (American Journal of Kidney Diseases, 2003)
Advanced glycation end products (AGEs) are formed during the nonenzymatic reaction of sugars with proteins. Conventional peritoneal dialysis fluids (PDFs) lead to the formation of AGEs in the peritoneal membrane that are associated with histopathologic changes and loss of ultrafiltration. PDFs may cause AGE formation because of a high glucose concentration or reactive glucose degradation products (GDPs), which are formed during heat sterilization of PDFs. This formation of GDPs is strongly pH dependent, which is exploited in newly developed double-chamber bag PDFs. Accordingly, 3-deoxyglucosone levels in double-chamber bag PDFs are reduced by approximately 80%, and levels of the GDPs acetaldehyde, formaldehyde, and methylglyoxal are less than the detection limit. Using an in vitro model that mimics regular changes in PDFs during continuous ambulatory peritoneal dialysis treatment, the contribution of high glucose versus GDP concentrations to AGE formation was investigated. The latter was determined by measuring protein bound N ε-(carboxymethyl)- lysine (CML) and imidazolone by enzyme-linked immunosorbent assay. In this model, more than 85% of imidazolone and more than 70% of CML were formed by GDPs, whereas only a minor part resulted from a high glucose concentration per se. New in vivo investigations suggest that GDPs from PDFs also can exert systemic effects after absorption into the blood circulation. Imidazolone levels in blood serum decrease significantly after switching from single- to double-chamber PDFs. In summary, the use of double-chamber PDFs may decrease not only local, but also systemic AGE formation. © 2003 by the National Kidney Foundation, Inc.
UnivIS-Import:2015-03-09:Pub.2003.nat.dchph.llmch.format_7
Keywords: Advanced glycation end products (AGEs); N epsilon-(carboxymethyl)-lysine (CML); continuous ambulatory peritoneal dialysis (CAPD); 3-deoxyglucosone (3-DG); glucose degradation products (GDPs); imidazolone